2010
DOI: 10.1007/s00276-010-0761-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bifid mandibular canals with cone-beam computed tomography in a Turkish adult population: a retrospective study

Abstract: This study, which utilized CBCT images, uncovered a higher prevalence of bifid mandibular canals than what has been reported in previous studies using conventional radiography techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
155
8
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(195 citation statements)
references
References 18 publications
17
155
8
15
Order By: Relevance
“…A higher prevalence of retromolar canals occurring bilaterally was observed in this study when compared to other reports in the literature, which have found a higher prevalence of right-sided retromolar canals 11,19,22,24 , though some authors have not observed differences between the right and left sides in dry mandibles 2 or in computed tomography images 8 . Notwithstanding that, other studies have demonstrated RMCs more frequently on the left side than on the right side 5,25 .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…A higher prevalence of retromolar canals occurring bilaterally was observed in this study when compared to other reports in the literature, which have found a higher prevalence of right-sided retromolar canals 11,19,22,24 , though some authors have not observed differences between the right and left sides in dry mandibles 2 or in computed tomography images 8 . Notwithstanding that, other studies have demonstrated RMCs more frequently on the left side than on the right side 5,25 .…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies using panoramic radiographs have reported incidences barely reaching 1% 16,17 . CBCT-based studies, however, have shown much higher values with prevalence rates ranging from 15.6% to 65% [18][19][20] . Therefore, conventional radiographs cannot be relied upon to detect anatomical variations of the mandibular canal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with panoramic radiographs reported incidences of less than 1% 6,9 . Studies with CBCT images have shown a much higher incidence, with prevalence ranging from 15.6% to 65% 2,[13][14][15] , thus reiterating that conventional radiographs are not suitable to detect anatomical variations of the mandibular canal. The differences in incidence may be related to ethnic, geographical as well as methodological differences.…”
mentioning
confidence: 99%
“…According to Neves et al 11 it is up to the dentist to recognize the possible anatomical variations of the mandibular canal in order to reduce the risk of failure during surgical or anesthetic approaches. For Orhan et al 13 knowledge of the anatomy of this canal is essential for successful dental interventions and regional mandibular anesthesia, as well as dental implant placement and jaw surgery.…”
mentioning
confidence: 99%
“…Recent studies employed CBCT images where Rashsuren et al, [11] Yang et al, [12] and Orhan et al [13] found the prevalence as high as 22.6%, 31.1%, and 46.5%, respectively, compared to the prevalence of 5.63% found in the present study using CBCT images. Sanchis et al [9] reported female predilection; however, in the present study, male predilection was found.…”
Section: Discussionmentioning
confidence: 44%